Role of Carnitine in Non-alcoholic Fatty Liver Disease and Other Related Diseases: An Update - Li, Na; Zhao, Hui (Frontiers in Medicine, 2021)
Carnitine is an amino acid-derived substance that coordinates a wide range of biological processes. Such functions include transport of long-chain fatty acids from the cytoplasm to the mitochondrial matrix, regulation of acetyl-CoA/CoA, control of inter-organellar acyl traffic, and protection against oxidative stress. Recent studies have found that carnitine plays an important role in several diseases, including non-alcoholic fatty liver disease (NAFLD). However, its effect is still controversial, and its mechanism is not clear. Herein, this review provides current knowledge on the biological functions of carnitine, the "multiple hit" impact of carnitine on the NAFLD progression, and the downstream mechanisms. Based on the "multiple hit" hypothesis, carnitine inhibits β-oxidation, improves mitochondrial dysfunction, and reduces insulin resistance to ameliorate NAFLD. L-carnitine may have therapeutic role in liver diseases including non-alcoholic steatohepatitis, cirrhosis, hepatocellular carcinoma, alcoholic fatty liver disease, and viral hepatitis. We also discuss the prospects of L-carnitine supplementation as a therapeutic strategy in NAFLD and related diseases, and the factors limiting its widespread use.